Location and Design Decisions of Facilities in a Distribution System with Elastic Customer Demand - 王雪峰 (Shanghai jiao tong da xue xue bao, 2009)
This paper describes a bi-level programming model that seeks to simultaneously optimize location and design decisions of facilities in a distribution system in order to realize company＇s maximal total profit subject to the constraints on the facility capacity and the investment budget. In the upper-level problem, twoechelon integrated competitive/uncompetitive capacitated facility location model, which involves facility location and design, is presented. In the lower-level problem, customer is assumed to patronize store based on facility utility which is expressed by service time cost in the store and its travel cost to customer. Customer＇s facility choice behavior is presented by a stochastic user equilibrium assignment model with elastic demand. Since such a distribution system design problem belongs to a class of NP-hard problem, a genetic algorithm （GA）-based heuristic procedure is presented. Finally, a numerical example is used to illustrate the application of the proposed model and some parameter sensitivity analyses are presented.